2022
DOI: 10.54855/ijte.22246
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Feedback on Using Discord as an Online Learning Platform

Abstract: The COVID-19 pandemic has called for a shift in the teaching and learning landscape from conventional classes to e-learning. This propels the use of a range of online learning and distance learning platforms massively, notably MS Teams, Zoom US, and Google Classroom. However, the fact that the aforementioned require a monetary subscription to unlock their full potential proves detrimental to the accessibility to education during the pandemic, i.e., not all students and/ or educational institutions have the ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Previous research demonstrated that Discord is an effective and free application converted for learning [24]. Additionally, it is utilized in lessons that positively impact student abilities, suitability, and satisfaction with the learning process [40].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research demonstrated that Discord is an effective and free application converted for learning [24]. Additionally, it is utilized in lessons that positively impact student abilities, suitability, and satisfaction with the learning process [40].…”
Section: Discussionmentioning
confidence: 99%
“…Most students can easily access and use the application since they have mobile devices. Discord has been adapted for educational purposes and has proven to be an efficient and free application [24]. It has been used in sport lessons and positively impacted students' ability, suitability, and satisfaction with their learning experiences [40].…”
Section: Discord Application For Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…It excels in online education by increasing student engagement and providing active opportunities for participation in the learning process (Pardines Lence et al, 2023;Wahyuningsih & Baidi, 2021;Wiles & Simmons, 2022). In addition, Discord was modified for educational purposes, evidencing its effectiveness as a free platform for this purpose (Uong et al, 2022). In developing countries, few educators adopt mobile teaching through technological tools like Discord to offer students a dynamic and interactive learning experience (Salehudin et al, 2023b).…”
Section: Discordmentioning
confidence: 99%
“…The reliance on a slow or unstable internet connection can disrupt the use of LMS and significantly impact the teaching and learning process. As Uong, Nguyen, and Nguyen (2022) claimed, the Internet connection is often one of the most popular challenges that teachers encounter when carrying out online learning activities.…”
Section: Challenges Of Using a Learning Management Systemmentioning
confidence: 99%